KAJIAN EPISTEMOLOGI BARAT Telaah Epistemologi Barat Fenemonelogi Hermeneutika dan Kritis: Telaah Epistemologi Barat Fenemonelogi Hermeneutika dan Kritis - Abdul Rohman, Moch (LPPM IAI Hasanuddin Pare-Kediri, 2023)
This paper examined the Western epistemology thought. The theme focuses on Plato to Gonseth thought. The Epistemology that referred in this article, is to think about